The impact of COVID-19 on community integration, quality of life, depression and anxiety in people with chronic spinal cord injury. (3rd September 2022) - García-Rudolph, Alejandro; Saurí, Joan; López Carballo, Jaume; Cegarra, Blanca; Wright, Mark Andrew; Opisso, Eloy; Tormos, Josep María
Abstract : Context/objective: Compare community integration, quality of life, anxiety and depression of people with chronic spinal cord injury (SCI) living in the community before the outbreak of coronavirus SARS-CoV-2 disease (COVID-19) and during it. Design: Prospective observational cohort study. Setting: In-person follow-up visits (before COVID-19 outbreak) to a rehabilitation hospital in Spain and on-line during COVID-19. Participants: Community dwelling adults (≥ 18 years) with chronic SCI. Outcome measures: Hospital Anxiety and Depression Scale (HADS), Community Integration Questionnaire (CIQ) and World Health Organization Quality of Life (WHOQOL-BREF) were compared using the Wilcoxon ranked test or paired t-test when appropriate. Results: One hundred and seventy five people with SCI assessed on-line between June 2020 and November 2020 were compared to their own assessments before COVID-19. Participants reported significantly decreased Social Integration during COVID-19 compared to pre-pandemic scores (P = 0.037), with a small effect size ( d  = −0.15). Depression (measured using HADS) was significantly higher than before COVID-19 (P < 0.001) with a moderate effect size ( d  = −0.29). No significant differences were found in any of the 4 WHOQOL-BREF dimensions (Physical, Psychological, Social and Environmental). Nevertheless, when all participants were stratified in two groups according to their age at on-line assessment, the younger group (19–54 years, N  = 85) scored lower during COVID-19 than before, in WHOQOL-BREF Physical (P = 0.004), ( d  = −0.30) and Psychological dimensions (P = 0.007) ( d  = −0.29). The older group (55–88 years, N  = 0) reported no significant differences in any dimension. Conclusions: COVID-19 impacted HADS' depression and CIQ's social integration. Participants younger than 55 years were impacted in WHOQOL-BREF's physical and psychological dimensions, meanwhile participants older than 55, were not.